Assessment and management of interfraction variations of lumpectomy cavities in accelerated partial breast irradiation - Chen, Xiaojian; White, Julia; Li, Wenhui; Ahunbay, Ergun; Currey, Adam; Bergom, Carmen; Kelly, Tracy; Wilson, J. Frank; Li, X. Allen (Therapeutic Radiology and Oncology, 2019)
Background: The purpose of this study is to quantitatively characterize interfraction variations of lumpectomy cavity (LC) in accelerated partial breast irradiation (APBI) and their dosimetric impacts, and to explore the use of an online adaptive replanning scheme to address these variations. Methods: A total of about 100 diagnostic-quality CT sets acquired using an in-room CT at each fraction during image-guided radiation therapy (IGRT) for ten randomly-selected patients treated with APBI in the supine position were analyzed. The LC, treated breast, lung and heart were delineated on each fraction CT. Organ volume change and deformation were quantified. For each fraction CT, three types of plans were created: adaptive, repositioning, and fully re-optimized plans. The plan qualities were compared.Results: Significant changes in LC shape and volume were observed during APBI. On average, the LC volume decreases by 23% from the planning CT. The average change in LC shape, as measured by the Dice’s coefficient, is 80%. For all patients, the adaptive plans were comparable to the re-optimization plans. For small and moderate LC changes (70%), the three types of plans were comparable, indicating that the current IGRT with the standard margins was sufficient to account for the interfraction variations. For cases with extreme LC change (30%), the adaptive plans offered improved target coverage and/or normal tissue sparing as compared with the repositioning plans. Conclusions: Significant variations in the LC between planning and treatment were found for APBI. The current practice of IGRT with standard planning target volume margins can account for these variations for most cases. Online adaptive replanning was needed for cases with extremely large changes in LC.